EMU enlargement, policy uncertainty and economic reforms - Carsten Hefeker (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper analyzes the relation between monetary uncertainty and government incentives to implement economic reforms that reduce structural distortions and make economies more flexible. It is shown that uncertainty about the central bank's reaction function leads to more reforms. I relate this result to the debate about central bank setup in a larger monetary union.
Keywords: D72; E52; E58; F33; 330